Anthropometric variables as predictors of speed in amateur football players / Zulkifli Ismail ... [et al.] - Ismail, Zulkifli; Wan Rosli, Wan Mohd Rashidi; Jamaludin, Masshera; Abu Talip, Nur Khairunisa; Miswan, Mohd Syafiq (Universiti Teknologi MARA, Perlis, 2020)
Speed is one of the important technical skills in football. Speed is defined as the ability of an athlete to move their self with maximum velocity from one place to another. The purpose of this study is to determine the predictor variables of speed ability in amateur football players and to present equation to predict speed ability. Fifteen (N=15) participants from Universiti Teknologi MARA (UiTM) Perlis FC, aged 20 ± 1 year were recruited for this study. The selected anthropometric variables were measured by different tests and instruments. The 20 m sprint test used to measure speed ability. The results showed a significant relationship was found between speed ability and body weight (r = 0.62), height (r = 0.71), waist circumference (r = 0.51), leg length (r = 0.52), foot length (r = 0.73), and fat free mass (r = 0.67) p ≤ 0.05. Speed ability might be predicted by the equation (r2 = 0.77) speed ability = -7.330 + 0.010 (Body Weight) + 0.058 (Height) + 0.028 (Waist Circumference) – 0.017 (Leg Length) + 0.095 (Foot Length) – 0.056 (Fat Free Mass). In conclusion, anthropometric variables are related to speed ability in amateur football players. Coaches and players should focus on the development of anthropometric variables associated with the speed to improve the speed ability.